Spatial analysis of vaccination coverage in Paraíba in 2016. (30th September 2020) - Martins, L; Cunha, N; Baebieri, C; Pamplona, Y; Loureiro, N; Olinda, R; Moschini, L
Abstract: Introduction: Immunization is a human right, being considered an action of the most successful and cost-effective in public health. In Brazil, it is an action that is linked to primary health care, In Brazil, the National Immunization Program (PNI), created in 1973, is recognized as a world reference of public health policy, as it offers all vaccines recommended by the World Organization health care in its national vaccination calendar. Objective: Spatial analysis of vaccination coverage of children aged 0 to 11 months in Paraíba in 2016. Methods: Cross-sectional study, with information on doses applied to children under 1 year of age obtained at the PNI, by municipality of Paraíba. Live birth data from the Live Birth information system (SINASC). Descriptive analysis, chi-square test, spatial analysis. Results: In Paraíba, 54.3% of the municipalities had adequate vaccination coverage, for BCG we have 68%, Hepatitis B (34.5%), Hib and DTP (35%), Polio (29.6%), pneumococcal (46.6%) and meningococcal (42.6%). The sertão paraibano is the mesoregion with the largest number of municipalities in the state with adequate vaccination coverage (p < 0.01), the paraiba forest is the region with the highest number of municipalities with very low coverage (p < 0.01). Conclusions: Thus, Paraíba does not present a homogeneous vaccination coverage, not having 'herd immunity'. This fact leaves the state vulnerable to the return of immunopreventable diseases and thus at risk of raising infant morbidity and mortality, constituting an important public health problem. Key messages: Immunization is a human right, being considered an action of the most successful and cost-effective in public health. Paraíba does not present a homogeneous vaccination coverage, not having 'herd immunity'.